Organic solar cells based on a novel infrared absorbing aza-bodipy dye - Mueller, T; Gresser, R; Leo, K; Riede, M (Elsevier, 2012)
For high efficiencies, organic solar cells have to harvest a large part of the solar spectrum. However, in particular for small molecule based cells, efficient infrared absorbers are still rare. We investigate here two aza-bodipy dyes which have promising properties. Upon benzannulation of the pyrrole of difluoro-bora-1,3,5,7-tetraphenyl-aza-dipyrromethene (Ph4-bodipy), the thin film absorption maximum is shifted by about 70–773 nm compared to the non-annulated molecule. The thin film properties of both materials are investigated and vacuum-processed solar cells using a mip-architecture (metal intrinsic p-doped) are compared. With the new benzannulated difluoro-bora-bis- (1-phenyl-indoyl)-azamethine (Ph2-benz-bodipy) as donor material, these planar heterojunction solar cells show an open-circuit voltage of 0.65 V, a fill factor of 65%, and an external quantum efficiency extending up to 860 nm. The mismatch corrected power conversion efficiency reaches 1.1%.